2015
DOI: 10.14712/23361964.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

A novel computational approach of image analysis to quantify behavioural response to heat shock in Chironomus Ramosus larvae (Diptera: Chironomidae)

Abstract: .: A novel computational approach of image analysis to quantify behavioural response to heat shock in Chironomus ramosus larvae (Diptera: Chironomidae) European Journal of Environmental Sciences, Vol. ABSTRACTAll living cells respond to temperature stress through coordinated cellular, biochemical and molecular events known as "heat shock response" and its genetic basis has been found to be evolutionarily conserved. Despite marked advances in stress research, this ubiquitous heat shock response has never been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Heat stress was administered by transferring larvae of both D. melanogaster and C. ramosus to incubators at 37 °C and 40 °C, respectively, in order to subject them to heat stress. Induction of HSP70 as well as responses of Chironomus (Nath and Lakhotia 1989;Nath and Gharpure 2015) and Drosophila (Lindquist 1980) were the criteria used in the present study for indicating heat stress, which indicates it occurs at 40 °C in C. ramosus and 37 °C in D. melanogaster.…”
Section: Heat Stressmentioning
confidence: 99%
“…Heat stress was administered by transferring larvae of both D. melanogaster and C. ramosus to incubators at 37 °C and 40 °C, respectively, in order to subject them to heat stress. Induction of HSP70 as well as responses of Chironomus (Nath and Lakhotia 1989;Nath and Gharpure 2015) and Drosophila (Lindquist 1980) were the criteria used in the present study for indicating heat stress, which indicates it occurs at 40 °C in C. ramosus and 37 °C in D. melanogaster.…”
Section: Heat Stressmentioning
confidence: 99%
“…Within the tube, larva shows a characteristic undulating movement that helps it draw water current across the tube for filter-feeding and gaseous exchange (Armitage et al, 1995;Nath and Gharpure, 2015). Meticulous observations by Walshe (1951) have further shown that inside the tube, the larva spins another funnel-shaped net along the anterior opening to capture detritus particles and planktonic organisms from the flowing stream of water.…”
Section: Regulation and Mechanism Of Silk Extrusionmentioning
confidence: 99%